The PaO2/FiO2 ratio on admission is independently associated with prolonged hospitalization in COVID-19 patients - Angelo Zinellu; Andrea De Vito; Valentina Scano; Panagiotis Paliogiannis; Vito Fiore; Giordano Madeddu; Ivana Maida; Elisabetta Zinellu; Arduino Aleksander Mangoni; Luigi Benedetto Arru; Ciriaco Carru; Sergio Babudieri; et al. (Journal of Infection in Developing Countries)
Introduction: The early identification of factors that predict the length of hospital stay (HS) in patients affected by coronavirus desease (COVID-19) might assist therapeutic decisions and patient flow management.